Role of various moving walls on energy transfer rates via heat flow visualization during mixed convection in square cavities. (15th March 2015) - Roy, Monisha; Roy, S.; Basak, Tanmay
Abstract: Mixed convection in closed cavities are important for various processing industries especially those associated with conservation of energy. Finite element based simulations are carried out for two cases based on the motion of the horizontal wall(s) (cases 1a–1d) or vertical wall(s) (cases 2a–2c). Heat flow distribution within the cavity enclosed by isothermally hot bottom wall, cold side walls and insulated top wall is analyzed for various fluids with Prandtl number, Pr = 0.026 and 7.2, Reynolds number, Re = 10–100 and Grashof number, Gr = 10 3 –10 5 . The direction of motion of wall(s) plays a significant role on the fluid flow field at Pr = 0.026, Gr = 10 3 and Re = 10 due to dominant forced convection for both horizontally (cases 1a–1d) or vertically (cases 2a–2c) moving wall(s). At Pr = 7.2, Gr = 10 5 and Re = 100, multiple convective heatline cells are observed for cases 1a–1d. It is found that, the strength of fluid or heatline circulation cells is less at Re = 100 compared to Re = 10 for cases 2a–2c due to weak buoyancy force at high Re . Energy transfer rates are assessed via local and average Nusselt numbers for cases 1a–1d and 2a–2c. Highlights: Mixed convection within square enclosures is important in many energy flow systems. Effect of motion of walls on the heat and fluid flow is studied. Energy flow via thermal management is analyzed based on heatline concept. Effect of various thermal parameters on trends of fluid and heat flow is examined. Enhanced heat flow rates are found to occur for various motion of walls.